Determination of parabens in water samples by cloud point extraction and aqueous two-phase extraction using high-performance liquid chromatography. Issue 47 (7th October 2016) - Noorashikin, M.S.; Mohamad, S.; Abas, M.R.
Abstract: Five methods have been successfully developed which are the ionic liquid–two-phase extraction (IL-ATPS), ionic liquid–two-phase extraction with addition of β-cyclodextrin as modifier (IL-βCD-ATPS), cloud point extraction (CPE-DC193C), cloud point extraction with addition of β-cyclodextrin as modifier (CPE-DC193C-βCD), and cloud point extraction with addition of ionic liquid functionalized β-cyclodextrin as modifier (CPE-DC193C-βCD-IL). These methods are new, green, and simple extraction technique to couple with a reversed-phase high-performance liquid chromatography to get the optimum conditions for phase separation of parabens in water samples. The parameters, i.e. pH of the solution, water content, distribution coefficient, and preconcentration factor, are evaluated to get the optimum conditions for phase separation of parabens. The CPE-DC193C-βCD-IL method shows the highest losses of water content among other methods. It also produces the highest preconcentration factor and distribution coefficient. The lowest limit of detection of parabens in water samples is also demonstrated by the CPE-DC193C-βCD-IL method. The CPE-DC193C-βCD-IL method gives an excellent performance on the detection of parabens from water samples with limit of detections are in the range of 0.017–0.043 μg/L with the percentage recoveries 90.5–98.9%. To conclude, the CPE-DC193C-βCD-IL method is a superior method in the determination of parabens from water samples among the developed methods. The use of β-CD is an economically viable approach because it improves the performance of paraben extraction method dramatically. In addition, this surfactant is cheap and non-toxic to our environment.